(untitled) (Eurasian Research Bulletin, 2023)
This article discusses the importance of developing moral and ethical education in students, given the current social conditions in our country, focusing on patriotism, independence, self-awareness, understanding the value of our homeland and people, recognizing one’s worth, seizing opportunities, and contributing to the prosperity of the nation and society. The article also explores contemporary approaches to fostering moral and ethical competencies in higher education, emphasizing their role in the successful development of every educational institution.